Reinterpreting Prophetic Communication for Ethical Islamic Da'wah in the Era of Generative AI - Ikhwansyah; Hasrat Efendi Samosir; Zhilla Jannati; Muhammad Randicha Hamandia (DAWUH : Islamic Communication Journal, 2026)
Abstract The rapid development of Generative Artificial Intelligence (Generative AI) has transformed the landscape of Islamic communication and da'wah practices in the digital era. This phenomenon not only offers new opportunities for disseminating Islamic messages but also raises ethical challenges related to authenticity, religious authority, algorithmic mediation, and the potential distortion of Islamic teachings. This study aims to reinterpret prophetic communication ethics as a normative framework for responding to the expansion of Generative AI in contemporary da'wah activities. This research employs a qualitative approach using the library research method by reviewing relevant literature concerning prophetic communication, digital da'wah, religious authority, social media, and artificial intelligence. Data were collected through documentation techniques and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that Generative AI has altered the patterns of Islamic communication, transformed the structure of religious authority, and increased the influence of platform algorithms in shaping audience behavior. In this context, prophetic communication values consisting of humanization, liberation, and transcendence become important ethical foundations to maintain authenticity, truthfulness, wisdom, and social responsibility in digital da'wah. This study proposes a reinterpretation model of prophetic communication that integrates Islamic ethical principles with the use of artificial intelligence technology to ensure that da'wah remains oriented toward public benefit and social harmony. Keywords: Prophetic Communication; Generative Artificial Intelligence; Islamic Da'wah; Digital Communication; Religious Authority.